2008
DOI: 10.1002/art.23318
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of six outcome assessment instruments in total shoulder arthroplasty

Abstract: Objective. To assess the responsiveness (sensitivity to change) of 6 shoulder outcome instruments. Methods. In a prospective cohort study of 153 total shoulder arthroplasties, outcome was measured by the Short Form 36 (SF-36); Disabilities of the Arm, Shoulder, and Hand questionnaire (DASH); Shoulder Pain and Disability Index (SPADI); American Shoulder and Elbow Surgeons questionnaire for the shoulder (ASES); and the Constant (Murley) Score (CS). Responsiveness was mainly quantified by effect sizes before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 29 publications
(39 reference statements)
5
114
1
6
Order By: Relevance
“…The measurement properties of the DASH have been extensively investigated. 2,8,15,43,47,53,72,118 The MDC has been reported to be between 6.6 and 12.2 points (weighted average, 10.5 points), 8,43,118 and the minimal clinically important difference has been reported to be 10.2 points. 115,118 The SPADI 112 is a 13-item patient self-report tool with 2 domains, 5 pain items, and 8 items of disability.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The measurement properties of the DASH have been extensively investigated. 2,8,15,43,47,53,72,118 The MDC has been reported to be between 6.6 and 12.2 points (weighted average, 10.5 points), 8,43,118 and the minimal clinically important difference has been reported to be 10.2 points. 115,118 The SPADI 112 is a 13-item patient self-report tool with 2 domains, 5 pain items, and 8 items of disability.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This last section is composed by one item related to pain and ten items related to function, and the validity, reliability, and responsivity of this section have been demonstrated. 27,28 The item related to pain is evaluated by a VAS (10 cm) that ranges from "no pain at all" to "pain as bad as it can be". The items related to function are evaluated by a four-point Likert scale.…”
Section: Translation and Cultural Adaptation To The Portuguese Languamentioning
confidence: 99%
“…Besides, studies have demonstrated that the ASES has better responsiveness than similar tools. 28 Besides providing a new tool for Brazilian rehabilitation professionals for clinical-and research-oriented uses, the Portuguese translation and cultural adaptation of the ASES will help standardize functional evaluation methods of the shoulder, similar to that of the methods used in other countries, allowing comparison of studies undertaken in different populations. Thus, the objective of the present study was to establish the Portuguese translation and cultural adaptation of the ASES to be used in patients with different shoulder disorders.…”
Section: Translation and Cultural Adaptation To The Portuguese Languamentioning
confidence: 99%
See 1 more Smart Citation
“…32 The SPADI questionnaire is a shoulder specific, responsive and valid measure of shoulder pain and disability. 33,34,35 When the SPADI questionnaire is used prior to treatment and then at discharge, the MDC is 18 points.…”
Section: Discussionmentioning
confidence: 99%